Body Mass of U.S. Hispanics/Latinos From the Hispanic Community Health Study/Study of Latinos (HCHS/SOL): How Do Diet Quality and Sedentary Time Relate?. (June 2020) - Perera, Marisa J.; Chirinos, Diana A.; Brintz, Carrie E.; Schneiderman, Neil; Daviglus, Martha; Talavera, Gregory A.; Perreira, Krista M.; Giacinto, Rebeca A. Espinoza; Qi, Qibin; Llabre, Maria M.
Little evidence exists on diet quality- and sedentary time-related differences in body mass index (BMI) among immigrant and nonimmigrant Hispanics/Latinos with different lengths of U.S. residence. A total of 13, 962 (80.2% foreign-born) Hispanic Community Health Study/Study of Latinos (HCHS/SOL) participants aged 18 to 60 from four U.S. cities (Bronx, NY; Chicago, IL; Miami, FL; and San Diego, CA) underwent standardized interviews and fasting blood tests. Diet quality was total Alternative Healthy Eating Index score. Sedentary time was number of <100 counts/minute over 3 to 6 days. BMI was examined using regression models adjusted for age, income, Hispanic/Latino background, HCHS/SOL site, and tobacco use. Two three-way interactions (diet or sedentary time length of residence sex) were tested to examine health behavior-related differences in BMI among immigrant and nonimmigrant males and females. The diet length of residence sex interaction was significant ( b = .005, 95% confidence interval [−.003, .008]). For a 10-unit Alternative Healthy Eating Index difference, the BMI difference was greater among immigrant females in the United States longer (0 years = .84 kg/m 2 ; 10 years = 1.64 kg/m 2 ). Diet-related obesity prevention efforts may start soon after migration, particularly for immigrant women.